#TITLE_ALTERNATIVE# - ARSYADANIE (NIM 12204061); Pembimbing: Dr. Ir. Pudjo Sukarno dan Amega Yasutra, M.S., ROBBIE
Coalbed Methane (CBM) reservoir is an unconventional gas reservoir which is formed during coalification process. The gas is adsorbed in inner surface of coal matrix. CBM reservoir usually contains water on its fracture, so high water production (dewatering prosess) that will decrease reservoir pressure should be conducted, before methane gas production. In a low reservoir pressure the gas will desorb from inner surface of coal matrix, and flow to the wellbore. As any production well, the design of well production operation needs well productivity, which is defined as the fluid flow rate to the wellbore is proportional to the difference between reservoir and well bottom hole pressures, the relationship is known as the IPR curves. The IPR curve for wells producing from CBM reservoirs had not been developed. Due to increase in energy demand and oil price, the alternative energy use become interesting including CBM, so the development of IPR curves for this kind of wells is highly needed. As previous researches on the IPR curves, the dimensionless IPR development is the main objective. For this purposes, CBM reservoir model is developed using commercial software (CMG). The model considers the CBM reservoir conditions, especially the occrences of matrices and fractures in the coal bed. The actual CBM reservoir data from Horseshoe Canyon Field in Canada, and Cedar Hill Field in New Mexico are applied to the model. For further development of dimensionless IPR curve, and six hypothetical data are introduced to the model. The model is validated using the Seidle King* and Cooper* equation,and gives satisfactory results. Using the reservoir and well data the dimensionless.